2013
DOI: 10.4103/0019-5049.108554
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative and intraoperative risk factors for early postoperative mechanical ventilation after scoliosis surgery: A retrospective study

Abstract: Background:Patients undergoing corrective surgery for scoliosis of spine are commonly ventilated in our institute after the operation. Postoperative mechanical ventilation (PMV) and subsequent prolongation of intensive care unit stay are associated with increase in medical expenditure and complications such as ventilator-associated pneumonia. Identification of factors which may contribute to PMV and their modification may help in allocation of resources effectively. The present study was performed to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…We found 11 retrospective studies reporting on 592 pediatric patients undergoing spinal fusion surgery, of whom 134/558 (24%) required prolonged mechanical ventilation, defined as !36 hours (see Table 2). [16][17][18][19][20][21][22][23][24][25][26] It was unclear how many of the patients in the paper by Mills et al remained extubated at !36 hours. 16 Twenty-three (2.5%) of the patients received HMV preoperatively.…”
Section: Predictors Of Prolonged Mechanical Ventilation Postsurgical mentioning
confidence: 99%
See 1 more Smart Citation
“…We found 11 retrospective studies reporting on 592 pediatric patients undergoing spinal fusion surgery, of whom 134/558 (24%) required prolonged mechanical ventilation, defined as !36 hours (see Table 2). [16][17][18][19][20][21][22][23][24][25][26] It was unclear how many of the patients in the paper by Mills et al remained extubated at !36 hours. 16 Twenty-three (2.5%) of the patients received HMV preoperatively.…”
Section: Predictors Of Prolonged Mechanical Ventilation Postsurgical mentioning
confidence: 99%
“…Zhang et al found surgical approach to be the only predictor of prolonged mechanical ventilation in their study, 24 while Gurajala et al found longer vertebral fusions and hypothermia to be associated with prolonged mechanical ventilation. 26 While there is evidence that the degree of impairment of pulmonary function correlates with the need for prolonged mechanical ventilation post-scoliosis repair, there does not appear to be a consensus on the defined cutoff level that best predicts the need for protracted ventilatory support.…”
Section: Predictors Of Prolonged Mechanical Ventilation Postsurgical mentioning
confidence: 99%
“…Hypothermia is the first thing come to mind that some studies report most scoliosis cases develop hypothermia delaying emergence, even they are poikilothermic postoperatively. 8 In a study by Gurajala et al, 102 scoliosis patients underwent surgery were followed up and postoperative mechanical ventilation need found to be high in patients with more than 8 vertebrae fused and in patients who are hypothermic intraoperatively. 8 The excess number of vertebrae fused with surgery is associated with increased duration of surgery and increased blood loss, thereby blood transfusion.…”
Section: Respiratory System Complicationsmentioning
confidence: 99%
“…8 In a study by Gurajala et al, 102 scoliosis patients underwent surgery were followed up and postoperative mechanical ventilation need found to be high in patients with more than 8 vertebrae fused and in patients who are hypothermic intraoperatively. 8 The excess number of vertebrae fused with surgery is associated with increased duration of surgery and increased blood loss, thereby blood transfusion. Therefore risk of developing lung injury related to transfusion is increased.…”
Section: Respiratory System Complicationsmentioning
confidence: 99%
See 1 more Smart Citation